Geochemical characteristics and hydrocarbon generation modeling of the Paleogene source rocks in the Qinnan Depression, Bohai Bay Basin, China - Lei, Chuang; Meng, Lingjian; Tian, Zehua; Ma, Qian; Wang, Qi; Fu, Jiang; Wei, Yaqiong (Frontiers in Earth Science, 2024)
The Qinnan Depression in the Bohai Bay Basin is lowly explored, where hydrocarbon generation potential of source rocks is required detailed investigation to identify hydrocarbon exploration potential and direction. This study is based on organic geochemical analysis performed on the Paleogene source rocks. After that, the burial, thermal maturity, and hydrocarbon generation histories of the Paleogene source rocks at various sags were reconstructed on BasinMod software based on reasonable geological models and geological parameters derived from geological analogy. Results show that the 3rd member (Es3) and 1st member (Es1) of the Eocene Shahejie Formation are high-quality source rocks with a mixture of type I and II kerogen, whose organic matter was originated from aquatic organisms under a reducing environment. The 3rd member (Ed3) of the Oligocene Dongying Formation are fair-quality source rocks with type II kerogen and are dominated by mixed organic matter depositing in a weakly reducing environment. Clear differences in hydrocarbon generation were observed in these three source rocks owing to differential subsidence and sedimentation among the Eastern, Southeastern, and Western sags. Source rocks at the Eastern Sag were maturated early and lasted for a long time, which were currently at late mature (1.0–1.3 %Ro) to high mature (1.3–2.0 %Ro) stages. Two hydrocarbon generation events occurred in the Oligocene and Miocene, respectively, with intensive hydrocarbon generation capacity. Source rocks at the Southeastern Sag were maturated late and lasted for a short period, which were currently at a medium mature (0.7–1.0 %Ro) stage. The major hydrocarbon generation event had occurred since the late Miocene, with intensive hydrocarbon generation capacity. Source rocks at the Western Sag were at an early mature (0.5–0.7 %Ro) stage and began to generate hydrocarbon in the Pliocene, with weak hydrocarbon generation capacity. The hydrocarbon generation capacity of the Paleogene source rocks is as follows: Es3>Es1>Ed3. The Qinnan Depression has high oil and gas exploration potential, where exploration activities should focus on effective traps around depression and slope zones located at the Eastern and Southeastern sags.